Electrical cardioversion of atrial arrhythmias with cardiac amyloidosis in the era of direct oral anticogulants. (28th July 2022) - Touboul, Olivier; Algalarrondo, Vincent; Oghina, Silvia; Elbaz, Nathalie; Rouffiac, Segolene; Hamon, David; Extramiana, Fabrice; Gandjbakhch, Estelle; D'Humieres, Thomas; Marijon, Eloi; Dhanjal, Tarvinder S.; Teiger, Emmanuel; et al.
Abstract: Aims: Atrial fibrillation (AF)/atrial flutter is common during cardiac amyloidosis (CA). Electrical cardioversion (EC) is a strategy to restore sinus rhythm (SR). However, left atrial thrombus (LAT) represents a contraindication for EC. CA patients with AF/atrial flutter have a high prevalence of LAT. We aimed to evaluate EC characteristics, LAT prevalence and risk factors, and AF/atrial flutter outcome in CA patients undergoing EC, predominantly treated with direct oral anticoagulants (DOACs). Methods and results: All patients with CA and AF/atrial flutter referred for the first time to our national referral centre of amyloidosis for EC from June 2017 to February 2021 were included in this study. In total, 66 patients (median age 74.5 [70;80.75] years, 67% male) were included with anticoagulation consisted of DOAC in 74% of cases. All patients underwent cardiac imaging before EC to rule out LAT. EC was cancelled due to LAT in 14% of cases. Complete thrombus resolution was observed in only 17% of cases. The two independent parameters associated with LAT were creatinine [hazard ratio (HR) = 1.01; confidence interval (CI) = 1.00–1.03, P  = 0.036] and the use of antiplatelet agents (HR = 13.47; CI = 1.85–98.02). EC acute success rate was 88%, and we observed no complication after EC. With 64% of patients under amiodarone, AF/atrial flutter recurrence rate following EC was 51% after a mean follow‐up of 30 ± 27 months. Conclusions: Left atrial thrombus was observed in 14% of CA patients listed for EC and mainly treated with DOAC. The acute EC success rate was high with no complication. The long‐term EC success rate was acceptable (49%).